2019
DOI: 10.3748/wjg.v25.i46.6713
|View full text |Cite|
|
Sign up to set email alerts
|

Aberrant methylation of secreted protein acidic and rich in cysteine gene and its significance in gastric cancer

Abstract: BACKGROUNDAberrant methylation in DNA regulatory regions could downregulate tumor suppressor genes without changing the sequences. However, our knowledge of secreted protein acidic and rich in cysteine (SPARC) and its aberrant methylation in gastric cancer (GC) is still inadequate. In the present research, we performed fundamental research to clarify the precise function of methylation on SPARC and its significance in GC.AIMTo investigate promoter methylation and the effects of the SPARC gene in GC cells and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…In support of our in vitro studies, the same inverse correlation between the hypermethylation of CpGs of SPARC promoter and its transcript levels was observed by analyzing 450K methylation array data for the CpG of SPARC for an independent cohort of 877 LUADs and 765 LUSC of TCGA dataset. Together, our data corroborate the link between methylation and expression of SPARC just observed in many other solid tumors [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…In support of our in vitro studies, the same inverse correlation between the hypermethylation of CpGs of SPARC promoter and its transcript levels was observed by analyzing 450K methylation array data for the CpG of SPARC for an independent cohort of 877 LUADs and 765 LUSC of TCGA dataset. Together, our data corroborate the link between methylation and expression of SPARC just observed in many other solid tumors [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…Subsequently, clinical studies have found that SPARC is a possible marker for diagnosing and prognosticating gastric cancer and an important factor regulating various signaling pathways (Wang et al, 2019). The SPARC gene acts to suppress epigenetic tumorigenesis (Shao, 2018). SPARC brings new targets and therapies to treat gastric cancer (Zhou, 2018).…”
Section: Regulatory Mechanisms Of Sparc In Gastric Cancermentioning
confidence: 99%